The dispersion–brightness relation for fast radio bursts from a wide-field survey. (18th October 2018) - Shannon, R.; Macquart, J.-P.; Bannister, K.; Ekers, R.; James, C.; Osłowski, S.; Qiu, H.; Sammons, M.; Hotan, A.; Voronkov, M.; Beresford, R.; Brothers, M.; et al.
Abstract Despite considerable efforts over the past decade, only 34 fast radio bursts—intense bursts of radio emission from beyond our Galaxy—have been reported1, 2 . Attempts to understand the population as a whole have been hindered by the highly heterogeneous nature of the searches, which have been conducted with telescopes of different sensitivities, at a range of radio frequencies, and in environments corrupted by different levels of radio-frequency interference from human activity. Searches have been further complicated by uncertain burst positions and brightnesses—a consequence of the transient nature of the sources and the poor angular resolution of the detecting instruments. The discovery of repeating bursts from one source3, and its subsequent localization4 to a dwarf galaxy at a distance of 3.7 billion light years, confirmed that the population of fast radio bursts is located at cosmological distances. However, the nature of the emission remains elusive. Here we report a well controlled, wide-field radio survey for these bursts. We found 20, none of which repeated during follow-up observations between 185–1, 097 hours after the initial detections. The sample includes both the nearest and the most energetic bursts detected so far. The survey demonstrates that there is a relationship between burst dispersion and brightness and that the high-fluence bursts are the nearby analogues of the more distant events found in higher-sensitivity, narrower-field surveys5 . A large-scale survey of fast radio bursts—short pulses of radio waves that seem to come from cosmological distances—finds 20 such events, including both the nearest and the most energetic bursts observed so far.